Exploring Near-Synonymy of the Adjectives ‘Expensive’ and ‘Costly’ through Corpus-Based Study - Intarajak, Kanjanapa; Kongduang, Theerapong; Bana, Clement Robles (Association of Language Teachers in Southeast Asia (ALTSA), 2025)
This study employed a corpus-based methodology to investigate the near-synonymous English adjectives ‘expensive’ and ‘costly’, with particular attention to their degree of formality, collocational pattterns, and semantic preferences. Drawing on data from the Corpus of Contemporary American English (COCA), which encompasses eight distinct genres (spoken, fiction, magazines, newspapers, academic texts, blogs, web pages, and TV/movie subtitles), the analysis focused on the frequency of use across genres and the most common noun collocates with Mutual Information (MI) scores of 3 or higher. The results indicated that ‘expensive’ occurred more frequently in informal genres such as blogs, magazines, and spoken texts, while ‘costly’ was predominantly found in formal contexts, especially newspapers and academic writing. Although some collocates overlapped, their semantic preferences differed: ‘expensive’ typically co-occurred with terms related to luxury products and personal choices, while ‘costly’ was associated with business, legal, and problem-related contexts. The findings revealed that the two adjectives, while semantically related, were not fully interchangeable. This distinction provided insight into how English learners could develop vocabulary precision through the use of corpus tools. The study concluded that corpus-based analysis was an effective method for highlighting subtle lexical differences, offering practical implications for language teaching and learning.